Numerical Modelling of Thin-walled Purlins Connection to the Supporting Structure. (2017) - Pařenica, Přemysl; Rosmanit, Miroslav; Flodr, Jakub
Abstract: The advantage of thin-walled cold-formed steel profiles used as a carrying member in building structures is their low weight, which results to both material savings and simple assembly. However, the design disadvantages because of their large slenderness, which influence the local and global stability, occur. This phenomenon can have a significant influence to the total loadbearing capacity in comparison with the hot-rolled cross-sections. One of the critical sections can be assign in the support, because of the large influence of local forces action. Therefore this article deals with numerical models of thin-walled purlins overlap connection to the supporting structure. Numerical models are done especially for tall and slender purlins connected both – directly through the bottom flange or through the web using standard clip connection. The numerical models are understood as basis for future experimental tests of similar load connections.